RELASI KRISTEN DAN ISLAM DALAM KERANGKA MODERASI BERAGAMA DI DESA HOYANE, KECAMATAN SEKO, LUWU UTARA - Rumbi, Frans Paillin; Paonganan, Semar (Moderatio: Jurnal Moderasi Beragama, 2024)
In this research, we use the notion of religious moderation to examine the relationship between Christians and Muslims in Hoyane village, Seko District, North Luwu. The perspectives of Christians are highlighted in this study. In the research locus, information was gathered via interviews and observation. To find out their opinions on dealing with Muslims, we spoke with leaders in the Christian community. The study's findings demonstrate that the existence of tabligh congregations strains ties between religions. Nonetheless, Christians attempt to live with this by maintaining their relationships with Muslims. Acknowledge the growing religious consciousness among Muslims and cultivate a welcoming and tolerant mindset. They also reinforce interfaith cooperation and unity through a cultural approach.